Cerebral Palsy Definition and Classification - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
A revised definition and classification of cerebral palsy is proposed by the Executive Committee of an International Workshop held in Betheda, MD, 2004.